Comparative transcriptome analysis and heterologous overexpression indicate that the ZjZOG gene may positively regulate the size of jujube fruit - Meiyu Li; Siqian Jiao; Pengqiang Yao; Yuanzhe Xie; Xiaolei Yang; Huijin Zhang; Hongju Yao; Junchao liu; Xiaoming Pang; Wenhao Bo; Shiping Cheng (BMC Plant Biology)
Abstract Background Fruit size is a crucial economic trait that impacts the quality of jujube (Ziziphus jujuba), however, research in this area remains limited. This study utilized two jujube cultivars with similar genetic backgrounds but differing fruit sizes to investigate the regulatory mechanisms affecting fruit size through cytological observations, transcriptome sequencing, and heterologous overexpression. Results The findings reveal that variations in mesocarp cell numbers during early fruit development significantly influence final fruit size. Comparative transcriptome sequencing identified 16,778 differentially expressed genes across five developmental stages. Co-expression network analysis identified 16 co-expression modules. KEGG enrichment analysis of these modules indicated the significant role of plant hormone-related pathways in fruit development. A detailed analysis of the ‘sky blue’ module revealed candidate genes associated with the regulation of mesocarp cells, leading to the construction of a regulatory network. Heterologous overexpression of the candidate gene ZjZOG in tomato confirmed its positive role in fruit size enhancement. Transcriptomic analysis of these overexpression lines further validated the regulatory network and identified reliable candidate genes for fruit size control. Conclusion This study provides valuable insights into the regulatory mechanisms of fruit size, which may facilitate the breeding of larger jujube cultivars.